Antecedents and consequences of health performance based on patient intimacy - Ryandono, Sri Herianingrum, Ririn Tri Ratnasari, Sri Gunawan, Muslich Anshori,Muhammad Nafik Hadi (Opción, 2019)
This study aims to determine the antecedents and consequences in order to improve the performance of health services based on the patient intimacy perspective on the ISO-certified community health centers via qualitative exploratory methodology and quantitative methodology explanation. The results of this study indicate that antecedents and consequences improve the performance of health services based on patient intimacy perspective at community health centers. In conclusion, strategic imperative can significantly affect the company’s bottom line and the company’s success.